MicroRNA profiling during germline differentiation of mouse embryonic stem cells - Ebrahimzadeh-Vesal, R; Shokrgozar, M A; Nayernia, K; Teimoori-Toolabi, L; Estiar, M A; Miryounesi, M; Nourashrafeddin, S; Modarressi, M H (Cellular and Molecular Biology, 2015)
MicroRNAs are new classes of small non”coding regulatory RNAs which control degradation or suppress translation of its target mRNAs by sequence complementarity. Mature microRNAs are enriched in embryonic stem cells and play important roles in controlling stem cell self”renewal as well as control of differentiation. There is significant evidence that microRNAs are involved in the regulation of stem cell differentiation. The male mouse Embryonic Stem Cell line C57BL6/J with normal karyotype 46, XY was used for profiling microRNA expression in undifferentiated mouse embryonic stem cells (mESCs) and mESCs which were differentiated to germ line cells to determine and compare differences in microRNA expression before and after differentiation. Also, testis tissue samples of a 5”day”old mouse and a mature mouse was used as in vivo control. Profiling was performed by quantitative real”time PCR using locked nucleic acid microRNA”specific LNATM”enhanced primers. After data analysis and comparison of results profiled microRNAs expression, three microRNAs, mmu”miR”21, mmu”miR”21* and mmu”miR”16 showed 50.31, 43.76 and 46.77”fold change increase of expression, respectively, in differentiated mESCs in comparison with undifferentiated state with significant p”value (Average p”value p<0.001 for each members of microRNAs). Expression of Let”7 microRNA family increased in differentiated state when compared with undifferentiated mESCs (Average p”value<0.0001 for each members of family). The levels of expression all other profiled microRNAs were significantly higher in undifferentiated in comparison with differentiated mESCs and their expression was down regulated after differentiation. (Average p”value <0.003 for each members of microRNAs).